2020
DOI: 10.1038/s41598-020-64431-4
|View full text |Cite
|
Sign up to set email alerts
|

Synovial tissue transcriptomes of long-standing rheumatoid arthritis are dominated by activated macrophages that reflect microbial stimulation

Abstract: Advances in microbiome research suggest involvement in chronic inflammatory diseases such as rheumatoid arthritis (RA). Searching for initial trigger(s) in RA, we compared transcriptome profiles of highly inflamed RA synovial tissue (RA-ST) and osteoarthritis (OA)-ST with 182 selected reference transcriptomes of defined cell types and their activation by exogenous (microbial) and endogenous inflammatory stimuli. Screening for dominant changes in RA-ST demonstrated activation of monocytes/macrophages with gene-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 71 publications
2
29
0
Order By: Relevance
“…RA sMacs have increased expression of TLR2 and TLR4 on their cell surface and when stimulated with DAMP ligands ex vivo, and secrete higher levels of pro-inflammatory factors (81,82). This correlates with a recent observation that synovial macrophages from established RA have a transcriptome profile similar to that observed in cells activated by pathogens (83). Sensitivity to these ligands can be further enhanced through exposure to oxidized oxysterols which are enriched in RA synovial fluid, resulting in increased secretion of proinflammatory factors (84).…”
Section: Macrophage Subsets In Rheumatoid Arthritissupporting
confidence: 80%
“…RA sMacs have increased expression of TLR2 and TLR4 on their cell surface and when stimulated with DAMP ligands ex vivo, and secrete higher levels of pro-inflammatory factors (81,82). This correlates with a recent observation that synovial macrophages from established RA have a transcriptome profile similar to that observed in cells activated by pathogens (83). Sensitivity to these ligands can be further enhanced through exposure to oxidized oxysterols which are enriched in RA synovial fluid, resulting in increased secretion of proinflammatory factors (84).…”
Section: Macrophage Subsets In Rheumatoid Arthritissupporting
confidence: 80%
“…Transcriptomic analysis of RA synovial tissue revealed activation patterns of infiltrating monocytes/macrophages. These patterns have corresponded to activation induced by microbial stimuli, whereas top proteins including MCP-1 and S100A8/A9 secreted by these cells in RA synovial tissue correlated with disease activity and reflected RA synovitis in blood [38]. Many research studies suggested that genetic contributions to RA disease susceptibility are not sufficient to completely explain the disease.…”
Section: Genetic Epigenetic and Environmental Factors Modulating Monocytes/macrophages In Ramentioning
confidence: 99%
“…Moreover, synovium CD14 expression correlated positively with disease activity (padj 0.016) (53,54). Along the same line, sCD14 levels are increased in RA synovial fluid and serum compared to osteoarthritis patients (55,56). sCD14 plays an important role in mediating the immune responses to LPS of CD14-negative cells such as endothelial cells and epithelial cells, and induces proinflammatory cytokines in fibroblast-like synovial cells from RA patients (57).…”
Section: Discussionmentioning
confidence: 85%